Targeted alpha therapy using astatine ((211)At)-labeled phenylalanine: A preclinical study in glioma bearing mice - Watabe, Tadashi (Oncotarget, 2020)
Phenylalanine derivatives, which target tumors especially through L-type amino acid transporter-1 (LAT1), have elicited considerable attention. In this study, we evaluated the treatment effect of phenylalanine labeled with the alpha emitter astatine ((211)At-PA) in tumor bearing mice. The C6 glioma, U-87MG, and GL261 cell lines were subjected to a cellular (211)At-PA uptake analysis that included an evaluation of the uptake inhibition by the system L amino acid transporter inhibitor 2-aminobicyclo-(2,2,1)-heptane-2-carboxylic acid (BCH). BCH significantly inhibited para-(211)At-PA uptake in C6 glioma (12.2 ± 0.8%), U-87MG (27.6 ± 1.1%), and GL261 (12.6 ± 2.0%) cells compared to baseline, suggesting an uptake contribution by system L amino acid transporters. Subsequently, xenograft and allograft models were prepared by subcutaneously injecting C6 glioma (n = 12) or GL-261 cells (n = 12), respectively. C6 glioma mice received three (211)At-PA doses (0.1, 0.5, or 1 MBq, n = 3/dose), while GL261 mice received one high dose (1 MBq, n = 7). (211)At-PA exhibited a tumor growth suppression effect in C6 glioma models in a dose-dependent manner as well as in GL-261 models. This phenylalanine derivative labeled with astatine may be applicable as an alpha therapy that specifically targets system L amino acid transporters.